Original and Modified Graeb Score Correlation With Intraventricular Hemorrhage and Clinical Outcome Prediction in Hyperacute Intracranial Hemorrhage. Issue 6 (June 2020) - Bisson, Daniel-Alexandre; Flaherty, Mathew L.; Shatil, Anwar S.; Gladstone, David; Dowlatshahi, Dar; Carrozzella, Janice; Zhang, Liying; Hill, Michael D.; Demchuck, Andrew; Aviv, Richard I.
Abstract : Background and Purpose—: The Graeb score is a visual rating scale of intraventricular hemorrhage (IVH) on noncontrast head CT. Little data exist in the hyperacute (<6 hour) period for reliability and predictive value of the modified Graeb Score (mGS) or the original Graeb Score (oGS) for clinical outcomes or their correlation with quantitative IVH volumes. Methods—: A retrospective analysis of multicenter prospective intracranial hemorrhage study was performed. oGS and mGS inter-observer agreement and IVH volume correlation on the baseline noncontrast head CT were calculated by intraclass correlation coefficient and Pearson coefficient respectively. Predictors of poor outcome (modified Rankin Scale scores ≥4) at 3 months were identified using a backward stepwise selection multivariable analysis. oGS and mGS performance for modified Rankin Scale scores ≥4 was determined by receiver operating characteristic analysis. Results—: One hundred forty-one patients (65±12 years) with median (interquartile range) time to CT of 82.5 (70.3–157.5) minutes were included. IVH was observed in 43 (30%) patients. Inter-observer agreement was excellent for both oGS (intraclass correlation coefficient, 0.90 [95% CI, 0.80–0.95]) and mGS (intraclass correlation coefficient, 0.97 [95% CI, 0.84–0.99]). mGS (R=0.79; P <0.01) correlated better than oGS (R=0.71; P <0.01) with IVH volumes ( P =0.02). Models of thresholded oGS and mGS were not different from a model of planimetric baseline intracranial hemorrhage and IVH volume for poor outcome prediction. Area under the curves were 0.70, 0.73, and 0.72, respectively. Conclusions—: Excellent correlation for oGS and mGS with IVH volume was seen. Thresholded oGS and mGS are reasonable surrogates for planimetric IVH volume for hyperacute intracranial hemorrhage studies.